PAKET WISATA EDUKASI SURABAYA ZOO VIRTUAL SEBAGAI INOVASI WISATA DI MASA PANDEMI COVID-19 : SURABAYA ZOO VIRTUAL EDUCATIONAL TOUR PACKAGE AS A TOURISM INNOVATION DURING THE COVID-19 PANDEMIC - Dyah Eka Noviyanti, Upik; Pratiwi, Fauziah Maulani; Santoso, Yuniawan Heru (PETA - Jurnal Pesona Pariwisata, 2024)
The Covid-19 pandemic has had an impact on the tourism sector, resulting in the closure of tourist attractions, such as the Surabaya Zoo tourist attraction. The impact of Covid-19 then gave birth to an innovation in virtual educational tour packages formed by the Surabaya Zoo team as an alternative for tourists to carry out tourism activities during the Covid-19 pandemic. The method used in the study was a descriptive qualitative approach method, with data collection techniques using primary data sources from interviews and observations, as well as secondary data sources from references, articles, journals, and websites. The Surabaya Zoo virtual educational tour package is one of the educational tour packages formed by the Surabaya Zoo during the Covid-19 pandemic. This package is intended for tourists who want to get to know animal life online, especially during the Covid-19 pandemic. The Surabaya Virtual Zoo educational tour package has 4 route options, of which 4 routes have differences, namely, the route passed, the animals explained, and the discussion spots. Virtual zoo educational tour activities are carried out through the online zoom meeting application with a duration of 90 minutes. Promotion of virtual zoo educational tour packages is done directly such as distributing brochures and contacting agencies, the second way is indirectly such as uploading on every social media. Keywords: Educational Tour, Innovation, Covid-19, Tour Packages, Virtual Tourism.